Application of 3D Printing Technology for Medical Purposes: A State of the Art - Pamungkas, Yuri; Kuswanto, Djoko; Syafira Eljatin, Dwinka; Nugroho Njoto, Edwin (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Introduction: The application of 3D printing technology in healthcare has revolutionized various medical practices, allowing for personalized solutions tailored to individual patient needs. This study explores the current state of 3D printing in medical applications, highlighting its benefits and challenges. Method: A comprehensive review of existing literature was conducted, focusing on the utilization of 3D printing for creating anatomical models, prosthetics, and bioprinting of living tissues. The analysis included a survey of various additive manufacturing techniques, such as Selective Laser Sintering (SLS) and Stereolithography (SLA), to assess their effectiveness in medical contexts. Results: The findings indicate that 3D printing enhances surgical planning by providing accurate anatomical models, thereby improving surgical outcomes. Additionally, the technology facilitates the production of custom implants and prosthetics, leading to better integration with patients' anatomy. Bioprinting has shown promise in developing artificial organs and regenerative therapies, significantly impacting transplant medicine. Discussion: While 3D printing offers substantial advantages, challenges such as regulatory hurdles, ethical considerations, and the need for standardized practices remain. The technology's potential in personalized medicine is vast, suggesting a future where individualized treatments are commonplace. Continued research and collaboration among medical professionals, technologists, and regulatory bodies are essential to address these challenges and optimize the benefits of 3D printing in healthcare. This study underscores the transformative impact of 3D printing in medicine and its potential to enhance patient care and outcomes across various applications.